Implementation of IoT-based SCADA in MPS Processing Station Integrated with CtrlX Automation - Maulana, Gun Gun; Mada, Ridwan; Rokhim, Ismail; Rudiansyah, Hendy; Suhada, Muhammad Giri (Jurnal Rekayasa Elektrika, 2025)
The increasing complexity of industrial automation technology today requires industries to upgrade their existing systems, such as IoT-based SCADA, which allows for real-time production monitoring from anywhere. However, to achieve this, a system is needed that does not affect or halt the production process and does not require replacing the existing system during the upgrade process. Therefore, a system that can adapt to the existing one is necessary. This research aims to implement an IoT-based SCADA system in an existing plant by integrating the system with ctrlX Automation to address this issue. The implementation is carried out in several stages. The first stage involves integrating the plant controlled by the Omron CP1L PLC with ctrlX Automation. The second stage is creating tags for the SCADA system using tools installed on ctrlX Automation. The third stage involves developing the user interface. The fourth stage is the remote access communication process for the IoT system using the OpenVPN Cloud tool. The test results show that the integration between the Omron CP1L PLC and ctrlX Automation was successful, with a 100% tag retrieval rate from the Omron CP1L PLC, and the data could be visualized. The user interface can be accessed, and remote access can be performed on different networks and locations using the OpenVPN Cloud tool. During testing, the average data transfer write-read delay with one address/tag during remote access was 61.3ms, and for the write-read test with three addresses simultaneously, the average was 78.1ms. Based on these results, the data transfer process using ctrlX Automation integrated with the Omron CP1L PLC can be categorized as very good.